Writing on the Wall: Street Art in Graffiti‐free Singapore. (28th September 2018) - Chang, T.C.
Abstract: The legalization of graffiti in many cities has impacted urban landscapes and the way artists and the public view graffiti, street art and the city as well. This article considers the genesis, process and consequences of legal walls programmes firstly by introducing and differentiating the key terms 'graffiti', 'street art' and 'legal walls', then by examining an empirical case, that of Singapore. Renowned as a graffiti‐averse and litter‐free city, Singapore's recent about‐turn in legalizing illicit art forms illustrates changing government perspectives on creativity and legality in the country. Why the government has effected this change, how artists and members of the public have responded to it and the resultant art forms are critically explored. The conclusion reflects on four key lessons from Singapore for cities in general.